Function of Proneural Genes Ascl1 and Asense in Neurogenesis: How Similar Are They? - Soares, Diogo S.; Homem, Catarina C.F.; Castro, Diogo S. (Frontiers in Cell and Developmental Biology, 2022)
Proneural genes were initially identified in Drosophila, where pioneer work on these important regulators of neural development was performed, and from which the term proneural function was coined. Subsequently, their counterparts in vertebrates were identified, and their function in neural development extensively characterized. The function of proneural transcription factors in flies and vertebrates is, however, very distinct. In flies, proneural genes play an early role in neural induction, by endowing neural competence to ectodermal cells. In contrast, vertebrate proneural genes are expressed only after neural specification, in neural stem and progenitor cells, where they play key regulatory functions in quiescence, proliferation and neuronal differentiation. An exception to this scenario is the Drosophila proneural gene Asense, which has a late onset of expression in neural stem cells of the developing embryo and larvae, similar to its vertebrate counterparts. Although the role of Asense remains poorly investigated, its expression pattern is suggestive of functions more in line with those of vertebrate proneural genes. Here, we revise our current understanding of the multiple activities of Asense and of its closest vertebrate homologue Ascl1 in neural stem/progenitor cell biology, and discuss possible parallels between the two transcription factors in neurogenesis regulation.